Globalisation and inflation in OECD countries - Gernot Pehnelt (European Centre for International Political Economy (ECIPE), 2007)
During the last two decades, the world has experienced a remarkable process of disinflation, with average inflation rates in industrialized countries falling by 10 percentage points and an even sharper decline of the mean rate of inflation in developing countries. Parallel to the decline in inflation rates, a tremendous increase in economic integration - often referred to as globalisation - has been taking place. In this paper, we analyse the effects of globalisation on inflation in OECD countries. We theoretically outline different channels through which globalisation may have influenced inflation dynamics and give an overview on the existing empirical evidence on this issue. In the empirical analysis we show that globalisation has contributed to the disinflation process in OECD countries since the 1980s. Inflation rates became much less prone to domestic parameters, especially the domestic output gap. Global factors such as the output gap of the main trading partners became more important in determining national inflation rates. Furthermore, economic freedom and the degree of globalisation are positively related to the disinflation process. Central bank independence seems to have contributed to the decline in inflation rates among OECD countries, but the effect is rather modest. Though the inertia of inflation can still be observed, the persistence of inflation has considerably declined since the early 1990s.
Keywords: E30; E31; E58; F41; 330; Inflation; globalisation; OECD countries; openness; panel analysis; Inflation; Globalisierung; Handelsliberalisierung; Deflation; OECD-Staaten